2022
DOI: 10.3390/nu14132631
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fermented Milk Containing Bifidobacterium animalis Subsp. lactis MN-Gup (MN-Gup) and MN-Gup-Based Synbiotics on Obesity Induced by High Fat Diet in Rats

Abstract: Given the probiotic effects previously found in Bifidobacterium animalis subsp. lactis MN-Gup (MN-Gup) and its great application potential in dairy products, this study aimed to investigate the effects of fermented milk containing MN-Gup or MN-Gup-based synbiotics on high fat diet (HFD)-induced obesity in rats. Galacto-oligosaccharides (GOS) and xylo-oligosaccharides (XOS) were selected as the tested prebiotics in MN-Gup-based synbiotics due to their promotion of MN-Gup growth in vitro. After nine weeks of HFD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…For example, fermented milk containing Lactobacillus gasseri SBT2055 could significantly reduce visceral fat, subcutaneous fat, and body weight gain in obese subjects ( 24 ), and fermented milk containing active L. reuteri NCIMB 30242 could reduce the levels of LDL-C and TC in patients with hyperlipidemia ( 25 ). In the previous study, fermented milk containing MN-Gup has been found to have the potential to treat obesity in rats ( 15 ), but the role of MN-Gup in preventing obesity has never been known. Previous studies mostly focused on the effects of probiotics on pre-existing obesity using therapy models, in which the mice or rats were firstly treated to reach a state of obesity, and then interventions of probiotics were performed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, fermented milk containing Lactobacillus gasseri SBT2055 could significantly reduce visceral fat, subcutaneous fat, and body weight gain in obese subjects ( 24 ), and fermented milk containing active L. reuteri NCIMB 30242 could reduce the levels of LDL-C and TC in patients with hyperlipidemia ( 25 ). In the previous study, fermented milk containing MN-Gup has been found to have the potential to treat obesity in rats ( 15 ), but the role of MN-Gup in preventing obesity has never been known. Previous studies mostly focused on the effects of probiotics on pre-existing obesity using therapy models, in which the mice or rats were firstly treated to reach a state of obesity, and then interventions of probiotics were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the preventive effects of MN-Gup and fermented milk containing MN-Gup on HFD-induced obesity were investigated in this study. Additionally, the current study investigated different objects and phenotypes by comparison with the previous study ( 15 ). The effects of various doses of MN-Cup were evaluated and the differences between MN-Gup powder and the corresponding MN-Gup-contained fermented milk were compared in the current study, while the previous study focused on the comparison between MN-Gup and its combination with prebiotics in fermented milk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by C. Wang et al investigates the effects of fermented milk containing Bifidobacterium animalis subsp. lactis MN-Gup (MN-Gup), which could alleviate HFD-induced body weight gain, epididymal fat deposition, adipocyte hypertrophy, dyslipidemia and inflammation, which may play important roles in the mechanism underlying the alleviation of obesity [ 4 ]. Meanwhile, Y. Huo et al found that Bifidobacterium animalis subsp.…”
Section: Obesity and Metabolic Disordersmentioning
confidence: 99%